Acquiring foreign firms far away might be hazardous to your share price: Evidence from Germany - Michael H. Grote; Fabian Rücker (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2007)
This paper examines shareholder wealth effects of cross-border acquisitions. In a sample 155 large acquisitions by German corporations from 1985-2006 international transactions total do not lead to significant announcement returns. Geography, however, makes a difference: Shareholders of acquiring firms gain 6.5% in cross-border transactions into countries that have a common border with Germany but lose 4.4% in other international transactions. We find proximity to be one of the most important success factors in cross-border and acquisitions, even when we control for firm, deal and country characteristics.
Keywords: 330; Börsenkurs; Übernahme; Multinationales Unternehmen; Entfernung; Deutschland